The Immune Response and Its Therapeutic Modulation in Bronchiectasis. (10th October 2012) - Daheshia, Massoud; Prahl, James D.; Carmichael, Jacob J.; Parrish, John S.; Seda, Gilbert
Abstract : Bronchiectasis (BC) is a chronic pulmonary disease with tremendous morbidity and significant mortality. As pathogen infection has been advocated as a triggering insult in the development of BC, a central role for the immune response in this process seems obvious. Inflammatory cells are present in both the airways as well as the lung parenchyma, and multiple mediators of immune cells including proteases and cytokines or their humoral products are increased locally or in the periphery. Interestingly, a defect in the immune system or suppression of immune response during conditions such as immunodeficiency may well predispose one to the devastating effects of BC. Thus, the outcome of an active immune response as detrimental or protective in the pathogenesis of BC may be dependent on the state of the patient's immunity, the severity of infection, and the magnitude of immune response. Here we reassess the function of the innate and acquired immunity in BC, the major sites of immune response, and the nature of the bioactive mediators. Furthermore, the potential link(s) between an ongoing immune response and structural alterations accompanying the disease and the success of therapies that can modulate the nature and extent of immune response in BC are elaborated upon.